A new epidioxy-tetracyclic triterpenoid from Poria cocos Wolf. Issue 15 (2nd August 2016) - Li, Shiping; Wang, Zhixin; Gu, Rui; Zhao, Yiwu; Huang, Wenzhe; Wang, Zhenzhong; Xiao, Wei
Abstract: A new epidioxy-tetracyclic triterpenoid, 3-(2-hydroxyacetoxy)-5 α, 8 α -peroxydehydrotumulosic acid (10 ), along with nine known compounds were isolated from Poria cocos Wolf (Polyporaceae). Their structures were determined by extensive spectroscopic analyses and comparison with literature data. The cytotoxicity of these compounds against human cancer cell lines MNK-45 was evaluated by MTT method. Abstract :